FACTORS INFLUENCING PARENTS' CHOICES ABOUT ENROLLING THEIR CHILDREN’S IN PRIVATE SCHOOLS (A CASE STUDY IN JALALABAD CITY) - Nazari, Qudratullah; Dadman, Enayatullah (American International Journal of Social Science Research, 2021)
The sight of this research paper was to examine the key components of impacting parent’s choice select privet schools for enrollment of their children’s, in Jalalabad city therefore this research paper was designed to find out the most important factors in the mention topic, otherwise for the collecting of data used survey method and the instrument of the data was interview with parents who choose privet schools for their children’s education level, the present study find out three most important factors which are security threats, digital education system, and teachers hiring, the result clearly indicate that privet schools are better for their children’s according to security sects, education level and teachers quality that are hire by education services providers, the findings also show that parents got great feedback from privet school services and they were satisfied from school administrations and schools staff, it is sagest for further researches that many more of factors will consider in this section.